AB0503 Therapeutic strategy and short-term outcome in neuropsychiatric systemic lupus erythematosus. (12th June 2018) - Bortoluzzi, A.; Fanouriakis, A.; Appenzeller, S.; Carli, L.; Carrara, G.; Conti, F.; Costallat, L.; De Marchi, G.; De Vita, S.; Doria, A.; Fredi, M.; Hanly, J.G.; et al.
Abstract : Background: The treatment of neuropsychiatric systemic lupus erythematosus (NPSLE) is extremely challenging and only a few clinical trials have been performed to establish optimal management. Objectives: To describe the therapeutic approach and the short-term outcome of a multi-centre cohort of patients with NPSLE, enrolled at the time of the first NP event. Methods: This is a retrospective cohort study. All NP events were defined according to American College of Rheumatology (ACR) case definition and divided into 3 clusters: central/diffuse (C/D), central/focal (C/F) and peripheral (P). A validated attribution algorithm was used to determine the attribution of all NP events. Demographic variables, global SLE disease activity Index 2000 (SLEDAI-2K), cumulative organ damage (SLICC/ACR Damage Index (SDI)) and treatment adopted for NP manifestations were collected. The clinical outcome of all NP events was determined by a physician-completed seven-point Likert scale (1=patient demise, 2=much worse, 3=worse, 4=no change, 5=improved, 6=much improved, 7=resolved). The relationship between the variables of interest and the outcome was analysed by crude and adjusted logistic models and reported as Odds Ratio (OR) and 95% confidence intervals (95% CI). Results: 461 SLE patients with at least one NP event were included. 91.8% of patients were female, mean (SD) age 35.4 (13.6) years. 19.7% (91) of events were observed at diagnosis of SLE, 13.4% (62) before and 66.8% (308) after the diagnosis. 111 events (24.1%) were C/F, 286 (62%) C/D and 64 (13.9%) P. 198 (42.95%) of all NP events were attributed to SLE. The overall probability of immunosuppressive therapy was 28.4% (95% CI 24.3–32.8), 38.7% (95% CI 29.6–48.5) in C/F, 21.3% (95%CI 16.7–26.5) in C/D and 42.2% (95%CI 16.7–26.5) in P manifestations. The probability of immunosuppressive therapy was 47.9% (95% CI 40.8–55.2) in attributed events. The one-year outcome was available in 355 patients. Physician assessment indicated resolution (76 patients) or improvement (150 patients) in 49% (226/461) of cases. The crude and adjusted OR of attributed NP events and immunosuppressants on a favourable outcome is illustrated in Figure 1. The multivariable logistic regression analysis was done adjusting for age at diagnosis of SLE [OR 0.96, 0.94–0.98] p=0.001, female gender [OR 0.97, 0.33–2.7] p=0.959, SDI [0.85, 0.68–1.08] p=0.202, SLEDAI-2K [1.06, 1.01–1.11] p=0.008 and type of event (F/C [REF], C/D [0.37, 0.16–0.83] p=0.016, P [0.54, 0.21–1.42] p=0.215). Conclusions: In our study, the therapeutic immunosuppressive approach was mostly used in attributed, C/F and P manifestations. In patients treated with immunosuppressants, the favourable outcome was lower in C/D phenotype. Disclosure of Interest: None declared